Modification of aggregation-prone regions of Arabidopsis glutamyl-tRNA reductase leads to increased stability while maintaining enzyme activity - Ji, Shuiling; Wang, Peng; Grimm, Bernhard (Frontiers in Plant Science, 2025)
The aggregation-prone region (APR) is a hydrophobic polypeptide motif that promotes protein aggregation, most commonly in the unfolded or misfolded state. It has been described that chaperones can shield the APRs of proteins, thereby preventing aggregate formation during de novo protein synthesis and stress response. Glutamyl-tRNA reductase (GluTR) is a key enzyme in tetrapyrrole biosynthesis (TBS) which catalyzes the rate-limiting step of 5-aminolevulinic acid synthesis. The GluTR sequence contains two APRs located at the N-terminus, which are suggested to be associated with the dysregulation of protein homeostasis during folding and refolding processes or under stress conditions. It remains open if these APRs directly contribute to GluTR aggregation in vivo, and how their removal or the modification might impact the aggregation and stability. In this study, we altered and removed the GluTR-APRs to investigate their effects on the stability and enzymatic activity of GluTR. Deletion of the APRs has been shown to be highly disruptive to the structure of GluTR, and a substitution mutation of V→P in each APR has also lowered the GluTR stability and activity. In contrast, the mutation V→T resulted in a modest reduction (18–30%) in GluTR aggregation in vitro, which was associated with a 27% improvement in GluTR stability in vivo relative to the wild-type enzyme. These results indicate that a point mutation in APR can improve GluTR stability without significantly affecting enzyme activity, thus imposing a potential direction for bioengineering of GluTR to improve productivity of the TBS pathway in plants.